Isotopic study of the rates of hydrogen provision vs. methanol synthesis from CO2 over Cu-Ga-Zr catalysts - Fornero, Esteban Luis (2015)
Cu/ZrO2 and Ga2O3-promoted Cu/ZrO2, with the same copper loading (2.6 wt.%), were evaluated in a Carberry-type batch-operated microreactor for methanol synthesis using a H2/CO2/He mixture (75/22/3 v/v) at 1.6 MPa and 498 K. The gallia-promoted catalyst was 5-fold more active to methanol production (per catalyst specific surface) than Cu/ZrO2. In addition, after the incorporation of Ga2O3 the selectivity to the alcohol was enhanced by a factor of three. To discern whether different degrees of hydrogen provision were responsible for the dissimilar performances observed, thus affecting the overall reaction rate to methanol (RCH3OH), the ability to activate H2 of the catalysts was assessed – in the same microreactor – by a combination of H2/D2 isotopic equilibration (H2/D2/Ar = 37.5/37.5/25 v/v) and H/D isotopic exchange (D2/Ar = 10/90 v/v) reactions at 0.1 MPa, between 353 and 393 K. The equilibration rate (Requil) was far higher than RCH3OH on both, Cu/ZrO2 and Ga2O3-promoted Cu/ZrO2. In agreement with the property of gallia to dissociate H2, Ga2O3 increased further Requil in the ternary catalyst. Vis-à-vis, the isotopic-exchange reaction rates (Rexchg) were considerably lower than the Requil for each catalyst, more so for the gallium containing one. However, the extrapolation of those Rexchg values to the temperature of methanol synthesis gave always much higher rates than RCH3OH, thus allowing to conclude that the supply of ‘active’ hydrogen is fully secured on these copper-supported (gallium-promoted) catalysts.